2022
DOI: 10.2147/dmso.s361808
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum Asprosin and Diabetic Nephropathy in Patients with Type 2 Diabetes Mellitus in the Community: A Cross-Sectional Study

Abstract: Objective To explore the association between serum asprosin and diabetic nephropathy (DN) in patients with type 2 diabetes mellitus (T2DM) in the community. Methods In this cross-sectional study, we retrospectively collected the clinical data of T2DM patients from a community health service center in southeastern Shanxi Province between November 2019 and July 2021. Logistic regression analysis was used to calculate the odds ratio (OR) and the 95% confidence interval (95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
(31 reference statements)
1
3
0
Order By: Relevance
“…Literature data showed a potential link between high circulating asprosin and uncontrolled diabetes that usually displays microvascular diabetic complications such as nephropathy, retinopathy, and peripheral neuropathy ( Table 4 ). As expected, circulating asprosin levels were significantly enhanced in T2DM patients with diabetic complications ( 67 , 68 , 70 , 71 ). Diabetic nephropathy (DN) (also known as diabetic kidney disease), a common severe complication of both types of diabetes mellitus, is considered a major cause of end-stage renal failure that seriously affects diabetic patients’ quality of life ( 76 ).…”
Section: Asprosin In Diabetic Complicationssupporting
confidence: 81%
“…Literature data showed a potential link between high circulating asprosin and uncontrolled diabetes that usually displays microvascular diabetic complications such as nephropathy, retinopathy, and peripheral neuropathy ( Table 4 ). As expected, circulating asprosin levels were significantly enhanced in T2DM patients with diabetic complications ( 67 , 68 , 70 , 71 ). Diabetic nephropathy (DN) (also known as diabetic kidney disease), a common severe complication of both types of diabetes mellitus, is considered a major cause of end-stage renal failure that seriously affects diabetic patients’ quality of life ( 76 ).…”
Section: Asprosin In Diabetic Complicationssupporting
confidence: 81%
“…Recently, the expression of asprosin in kidney tissues was reported [8]. Many studies demonstrated the changes in asprosin levels and their association with renal function in diabetic nephropathy cases that involved several pathogenic mechanisms [9][10][11]. The present study is the first in demonstrating the changes in asprosin levels in a rhabdomyolysisinduced AKI rat model.…”
Section: Discussionmentioning
confidence: 49%
“…Asprosin has been shown to have an inflammatory effect as it correlated positively with inflammatory cytokines and upregulated the inflammatory JNK phosphorylation TLR4-dependent pathway [9]. Also, it was found that increased levels of circulating asprosin were associated with diabetic nephropathy and that asprosin may affect renal homeostasis via several pathogenic mechanisms such as inflammation, insulin resistance, and endothelial dysfunction [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, an elevated level of asprosin also increases the risk of diabetic retinopathy 6 and diabetic nephropathy 7 . Further studies by our research group have found that the risk of diabetic nephropathy caused by elevated asprosin was closely related to gender, especially being female 8 . Nevertheless, its specific mechanisms are not yet fully understood.…”
Section: Introductionmentioning
confidence: 91%